Mean Residence Time and Dispersion Number Associated with Slurry Injection Methods in Chemical Mechanical Planarization. (1st January 2016) - Mu, Yan; Han, Rouchen; Sampurno, Yasa; Zhuang, Yun; Borucki, Leonard; Philipossian, Ara
Abstract : Slurry mean residence time, dispersion number, removal rate, coefficient of friction, and pad temperature were analyzed for standard pad center area slurry application and two configurations ("Design A" and "Design B") of the novel slurry injection system (SIS) used in chemical mechanical planarization. The novel SIS was placed on the pad surface and slurry was injected through an inlet port which matched an outlet at the trailing edge of the injector bottom. SIS having "Design A" has flat leading edge to prevent, as much as possible, spent slurry or residual water from re-entering the pad-wafer interface. In contrast, "Design B" possesses several notches on its leading edge for the temporary accumulation of a small amount of spent slurry. Results showed both configurations of the novel SIS generated lower coefficient of friction and pad temperature, shorter slurry mean residence time, smaller dispersion number and higher removal rate than the standard pad center area slurry application method. "Design B" has a higher mean residence time and larger dispersion number than "Design A" since "Design B" allows more spent slurry/residual rinse water to re-enter the pad-wafer interface than "Design A". This work underscores the importance of slurry injection method for achieving optimum chemical mechanical planarization processes.